Contesting precarity in Japan the rise of nonregular workers and the new policy dissensus - Shibata, Saori, 1973- (2020)
"Drawing on a new dataset charting protest events from the 1980s to the present, this book produces a systematic study of the new precarious labor movement that has developed during Japan's post-bubble neoliberal economic transformation"-- Provided by publisher
Keywords: Precarious employment -- Social aspects -- Japan.; Labor policy -- Japan.; Labor market -- Japan.; Neoliberalism -- Japan.; Japan -- Economic conditions.; Travail précaire -- Aspect social -- Japon.; Travail -- Politique gouvernementale -- Japon.; Marché du travail -- Japon.; Néo-libéralisme -- Japon.; Japon -- Conditions économiques.; POLITICAL SCIENCE -- Labor & Industrial Relations.; Economic history; Labor market; Labor policy; Neoliberalism; Japan